Improving the Students’ Speaking Ability Through Problem-Based Learning at SMK Negeri 2 Malinau : A Classroom Action Research - Akbar Ginandar; Dwiyani Pratiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the English speaking skills of students in class XI DPIB B at SMK Negeri 2 Malinau through the application of the Problem-Based Learning (PBL) model. The background of this research is the low speaking ability of students, which is characterized by limited vocabulary, lack of confidence, and low participation during English learning activities. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 32 students of class XI DPIB B. Data were collected through speaking performance tests and observations of students’ learning behavior during the implementation of the PBL model. The collected data were analyzed using quantitative and qualitative techniques. The results showed a significant improvement in students’ speaking skills, as indicated by the increase in the average score from 64.00 in the pre-test to 68.75 in cycle I and 76.00 in cycle II. Furthermore, the percentage of learning completeness increased from 25% in the pre-test to 81.25% at the end of cycle II. Observational data also revealed positive changes in students’ learning behavior, including higher participation, increased motivation, and greater confidence in speaking English. These findings demonstrate that the Problem-Based Learning model is effective in improving students’ English speaking skills and learning engagement.